The Implementation of Inclusive Education In Forming Students' Characters - Muhammad Noor Bin Ali; M. Athoiful Fanan; Amriana Amriana (IJIBS, 2023)
This research discusses the implementation of inclusive education as a basis for shaping the character of students at the Mamba'us Sholikhin Suci Gresik Islamic Boarding School. This research paradigm uses a phenomenological paradigm, a qualitative approach, with a case study type. Data collection techniques use three types of strategies, namely qualitative interviews, qualitative observation, and qualitative documents. This research suggests that the implementation of inclusive education as a basis for forming the character of students is carried out in the form of implementing the Islamic boarding school program by implementing a curriculum that adopts a combination of salaf and modern systems that are oriented towards Gontor and Langitan Islamic boarding schools as the mecca of Arabic and English mastery programs as daily languages. - Santri day, while Langitan Islamic boarding school is the mecca of the Mambaus Sholihin Islamic boarding school in terms of its Salafiyah curriculum, besides that with the Tahfidz Quran, Tahfidz mutun, bahtsul masail fiqhiyyah, munaqosyah nahwiyyah programs.